Supply Chain Practices and Performance of Institutions: A Case Study of Hotloaf Bakery in Kabale Municipality. - Asiimwe, Elias (Kabale University, 2023)
The study examined the efficient supply chain practices and performance of institutions: a case study of a hotloaf bakery in Kabale Municipality. The objectives of the study were; to identify the role of planning on timely production in hotloaf bakeries, to assess the relationship between sourcing and quality product output in hot loaf bakeries, and to investigate the impact of distribution on increased sales in hot loaf bakeries in Kabale municipality. A descriptive research design was used and data was collected using interviews and questionnaires. The study results on the roles of efficient planning on timely production in hotloaf bakery was; efficient planning helps in setting the priorities, efficient planning allows managers to evaluate, control, budget and improve different aspects of an organization, efficient planning helps in defining the organizational levels and standards, planning of bakery provides essential feedback to employees and the organization on areas they need to improve and efficient planning helps organization to establish an evaluative frameworks that captures overall organizational goals. The study results on the relationship between efficient sourcing and quality product output in hot loaf bakery where; outsourcing can be used to economize on production cost, outsourcing help bakeries to stay competitive, outsourcing allows bakeries to expand efficiency, outsourcing minimizes business expenditure for quality production, outsourcing helps to improve on bakery productivity and outsourcing helps in not giving attention other aspects of the business that do not deal with the core business functions. The study results on the impact of efficient distribution on increased sales in hot loaf bakery in Kabale municipality was; that efficient distribution makes products or services available for use which leads to increased sales, using the right distribution strategy helps in marketing and has a serious impact on business' future success due to increased sales, better distribution channels leads to increased market share and sales volume, efficient distribution involves wholesalers, distributors, and third parties to supply the products customers which lead high sales and efficient distribution is cost-effective in the bakery sales which leads high sales of the bakery. The study recommends that the process of strategic planning should be given its deserved attention in terms of all the prescribed steps to ensure an efficient supply chain and performance of the organization Hotloaf bakery should set performance targets and the preceding process of strategic planning it is an important aspect of performance management for their organization.